National Political Differences as a Cause of Debate Between the Pharisees and Jesus - Supratikno, Agus (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2024)
The prevailing view of the frequent debates between Jesus and the Pharisees was based on Jesus’ criticism of their hypocrisy and formalism. However, if we look further, the debate was also caused by the contrasts between the national political vision of Jesus and the Pharisees regarding Israel’s National Identity. This research explores that the debate between Jesus and the Pharisees is also caused by the differences between the national vision of Jesus and the Pharisees regarding the national identity of Israel in the 1st Century. This research used hermeneutical methods and library research with nation-state theory. This research proved that the sharp contradictions in the national visions of the Pharisees and Jesus regarding Israel’s national identity were also the cause of their frequent debates. The national political vision of the Pharisees was based on “Imitatio Sanctitatis Dei,” which was interpreted as separation, so it was exclusive. Jesus’ national vision was based on “Imitatio Misericordiae Dei,” which was inclusive. Through this research, it can be concluded that the debate between Jesus and the Pharisees was not only caused by Jesus’ criticism of formalism and hypocrisy but was also caused by contradictions regarding their national political vision of Israel’s national identity.